Omics Studies for the Identification of Ascidian Peptides, Cognate Receptors, and Their Relevant Roles in Ovarian Follicular Development - Kawada, Tsuyoshi; Osugi, Tomohiro; Matsubara, Shin; Sakai, Tsubasa; Shiraishi, Akira; Yamamoto, Tatsuya; Satake, Honoo (Frontiers in Endocrinology, 2022)
Omics studies contribute to the elucidation of genomes and profiles of gene expression. In the ascidian Ciona intestinalis Type A (Ciona robusta), mass spectrometry (MS)-based peptidomic studies have detected numerous Ciona-specific (nonhomologous) neuropeptides as well as Ciona homologs of typical vertebrate neuropeptides and hypothalamic peptide hormones. Candidates for cognate G protein-coupled receptors (GPCRs) for these peptides have been found in the Ciona transcriptome by two ways. First, Ciona homologous GPCRs of vertebrate counterparts have been detected by sequence homology searches of cognate transcriptomes. Second, the transcriptome-derived GPCR candidates have been used for machine learning-based systematic prediction of interactions not only between Ciona homologous peptides and GPCRs but also between novel Ciona peptides and GPCRs. These data have ultimately led to experimental evidence for various Ciona peptide-GPCR interactions. Comparative transcriptomics between the wildtype and Ciona vasopressin (CiVP) gene-edited Ciona provide clues to the biological functions of CiVP in ovarian follicular development and whole body growth. Furthermore, the transcriptomes of follicles treated with peptides, such as Ciona tachykinin and cionin (a Ciona cholecystokinin homolog), have revealed key regulatory genes for Ciona follicle growth, maturation, and ovulation, eventually leading to the verification of essential and novel molecular mechanisms underlying these biological events. These findings indicate that omics studies, combined with artificial intelligence and single-cell technologies, pave the way for investigating in greater details the nervous, neuroendocrine, and endocrine systems of ascidians and the molecular and functional evolution and diversity of peptidergic regulatory networks throughout chordates.